Debt-equity decision-making with wealth transfers. Issue 12 (1st December 2014) - M. Hull, Robert; M. Hull, Robert
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to instruct advanced business students on the debt-equity choice by showing how wealth transfers between security holders influence security values when a levered firm undergoes an incremental debt-to-equity approach. Design/methodology/approach – The design involves a pedagogical exercise that applies gain to leverage (GL) formulas for a firm aspiring to increase its value by exchanging debt for equity. The valuation method includes perpetuity formulations including those with growth and wealth transfers. The instructional approach offers an understanding of the debt-equity decision. Findings – Unlike studies that provide empirical findings or new theories, this paper provides knowledge and skills for students learning capital structure decision making. Research limitations/implications – All GL equations in this paper are limited by derivational assumptions and estimation of values for variables. Practical implications – This paper bridges the gap between theory and practice by illustrating the impact of the costs of borrowings, growth rates and risk shifts on debt-equity decision making. Students will learn and apply GL equations. They will get an appreciation for the practical complexities of financial decision making including the agency complication embodied in wealth transfers. Social implications – Society can be enhanced to the extent this paper helps future financial managers make optimal capital structure decisions. Originality/value – This paper adds to the Capital Structure Model (CSM) pedagogical research by using the new CSM equations that address a levered situation and incremental approach. As such, it is the first CMS instructional paper to incorporate wealth transfers between security holders.